Measuring reliability and validity of instrument: the dimensions of advertising literacy in determining the advertising literacy index - Neesa Ameera Mohamed Salim,; Mohd Yusof Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Advertising literacy has been a topic of discussion for decades long and up till today, the subject is still debated on. In fact, the dimensions of advertising literacy have evolved along with its many factors and varied key terms. Thus, this study was conducted to identify the key dimensions intact with advertising literacy through the use of factor analysis with the objective of measuring the reliability and validity of the dimensions present in advertising literacy. A survey was conducted at three locations of the Public’s Housing Program (PHP) in Kuala Lumpur to accumulate the response of this study. The use of the Exploratory Factor Analysis (EFA) with varimax rotation revealed that there are four factors which determines the advertising literacy index. Initially, a factor analysis on the 4 dimensions with 41 items was done and this showed that the numbers of dimensions are retained, yet, only 22 items could be measured. The results of this analysis contributed to the study by determining the reliability and validity of the four dimensions of advertising literacy; informational, visual, rhetorical and promotional literacy is applicable to other studies. In addition to this, it develops awareness towards the people in the advertising industry mainly the advertisers on how to maximise their advertising strategy by understanding the targeted audience intended in a deeper sense.